Vocabularies for an Urbanising Planet : Theory Building Through Comparison - Schmid, Christian; Streule, Monika (Birkhäuser, 2023)
Cartography as an instrument for the analysis of urbanisation processes The speed, scale and scope of urbanisation have increased dramatically in recent decades. To decipher the rapidly changing urban territories across the planet, we need a radical shift in the analytical perspective on urbanisation. In this book, a transdisciplinary international research team presents an expanded vocabulary of urbanisation processes through a comparison of Tokyo, Hong Kong - Shenzhen - Dongguan, Kolkata, Istanbul, Lagos, Paris, Mexico City and Los Angeles. Based on a novel cartography and on detailed ethnographic and historical explorations, this book systematically analyses the diversity of responses to urgent contemporary urban challenges. It proposes a series of new concepts that allow us to assess the practical consequences of different urban strategies in everyday life. Essential book on urbanism New evaluation models for urbanisation processes Comprehensive analyses and illustrations of the urban patterns of international metropolises Comparison of urbanisation processes in eight metropolises around the world